A case of treatment-resistant erosive pustular dermatosis of the scalp - Zahra Rehan; Tracey Brown-Maher (SAGE Open Medical Case Reports)
Erosive pustular dermatosis is a rare and chronic inflammatory condition of the scalp which can be mistaken for cutaneous malignancy, precancerous lesions, dermatitis or pyoderma gangrenosum. The recurrent and resistant characteristics of erosive pustular dermatosis of the scalp pose a challenge to successful management and remission of the condition. The purpose of this case report is to provide management options and treatment recommendations for refractory cases of erosive pustular dermatosis of the scalp. We report a case of erosive pustular dermatosis of the scalp that proved resistant to treatment, with various therapeutic modalities explored to address the persistent condition. In our patient, multiple treatment modalities included topical and oral corticosteroids, topical and oral antibiotics, topical vitamin D analogue, topical calcineurin inhibitor and oral isotretinoin. Based on our findings, refractory disease progression of erosive pustular dermatosis of the scalp may be more responsive to combination therapy rather than monotherapy.